1970
DOI: 10.3329/bjm.v24i1.1242
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Analysis of Some Raw Fish Samples

Abstract: Total load of bacteria, fungi and pathogenic microorganisms in muscle-and-skin samples of 12 different species of fish were analyzed. Highest standard plate count (5.1 x 106 cfu/g) was observed in Batashi (Clupisoma atherinoides) and lowest (2.3 x 105 cfu/g) in Rui (Labeo rohita). Total bacterial load was almost similar in case of other fishes. Mold count was highest (7.5 x 102 cfu/g) in shrimp (Penaeus indicus) and lowest (8.0 x 101 cfu/g) in Pabda (Ompok pabda). Yeast count varied between 1.0 x 103 cfu/g in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…Hall markets are not of good quality and are unsafe for consumption. The results correlates with earlier works [7,17]. The contamination of fishes may be due to environmental conditions during transportation to landing centers and whole sale markets through handling process that may be associated with infection [7,17,18].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Hall markets are not of good quality and are unsafe for consumption. The results correlates with earlier works [7,17]. The contamination of fishes may be due to environmental conditions during transportation to landing centers and whole sale markets through handling process that may be associated with infection [7,17,18].…”
Section: Resultssupporting
confidence: 89%
“…The results correlates with earlier works [7,17]. The contamination of fishes may be due to environmental conditions during transportation to landing centers and whole sale markets through handling process that may be associated with infection [7,17,18]. The bacterial count in April revealed that E. coli was higher on freshwater fishes when compared to March.…”
Section: Resultssupporting
confidence: 88%
“…Fishes play an important role in human diets as good sources of animal protein that also provide other important elements necessary for the maintenance of healthy bodies (Dewi et al, 2011;Ravichandran et al, 2012). Because of its high nutritive value, sea fishes are a major vehicle for pathogenic microorganisms (Das et al, 2007;Geetha et al, 2014). Fishes begin hostile by both the aquatic environment and post-harvesting condition (Al-Sheraa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…During transportation of these fish to land and wholesale market, the fish may also infect people associated in handling. When the consumers purchase these fish, they (fish with high bacterial load) are definitely transferred to the person who carries out them (Das et al 2007). Biological contaminants constitute the major cause of food borne diseases ranging from mild indisposition to chronic or life threatening illness (Phyllis 2007) and spoil food, including fish, meat, fresh fruits and vegetables (Pelczar et al 1986).…”
Section: Introductionmentioning
confidence: 99%